General Pharmacology of the Butanamide Derivative S 19812, a New Dual Inhibitor of Cyclooxygenase and Lipoxygenase Pathways - Tordjman, Charles; Andre, Nathalie; Bresson, Yvette; Bellot, Isabelle; Deschamps, Christine; Pastoureau, Phlippe; Wierzbicki, Michel (Arzneimittelforschung, 2003)
S 19812 (N-hydroxy-N-methyl-4-(2,3-bis-(4-methoxyphenyl)-thiophen-5-yl) butanamide, CAS 181308-68-9), a dual inhibitor of cyclooxygenase and lipoxygenase pathways, was evaluated in different models of pain and inflammation. Its gastric tolerance was also investigated. After acute oral treatment S 19812 exhibited a non-opioid analgesic activity observed in the phenylbenzoquinone-induced writhing model in mice (ED50 =2.1 mg/kg) and in the carrageenan-induced hyperalgesia model in rats (ED50 =9.1 mg/kg, preventive treatment; 8.3 mg/kg, curative treatment). Anti-inflamma-tory activity was observed in the adjuvant-induced arthritis in rat (inhibition of edema ED50 = 11 mg/kg/day p.o., day 28). In rats and mice, S 19812 exhibited an excellent gastric tolerance at doses up to 800 mg/kg p.o.
Keywords: Butanamide derivative; CAS 181308-68-9; Cyclooxygenase; Lipoxygenase; S 19812, gastrointestinal; tolerance, general pharmacology